A study on demograpic background that influence learning style among bachelor students at UiTM Pahang / Meor Fairuz Hazlee Rosli, Mohd Idzham Izainie Razali and Zulkamal Hassan - Rosli, Meor Fairuz Hazlee; Razali, Mohd Idzham Izainie; Hassan, Zulkamal (2012)
Learning styles can be defined as various approach or ways of learning, their involve educating methods, particular to an individual, that are consider to allow that individual to learn best (Kirby, 2007). He also mentioned that the term "learning style" came into use when researchers began to look for ways to combine course presentation and materials to match the needs of each learner (Lardner, 2006). Diagnosing and interpreting learning styles provide important data as to how individuals perceive, interact with, and respond to the learning environment (Griggs, 2006). However, it is important for students to realize that they are likely to do better in college if they consciously develop a variety of learning style more fully (Diana, 2008). It is important for student to recognize which learning styles they preferred to use so that they might have a better understanding of their own preferences (James, 2009). Through a better understanding of learning style student may begin to strengthen other modes of learning which may not come naturally to them (James, 2009). In this way, they might be more successful in any learning situation, regardless of the teaching style (Diana, 2008). This chapter will discussed further about the background of the study, problem statement, research objective, research question, significance of the study and the terminology will be addressed. This research will touch on the demographic background that may influence learning style among bachelor students' of UiTM Pahang.